HUBUNGAN SELF CONFIDENCE DENGAN PRESTASI BELAJAR BAHASA INDONESIA DI TINGKAT SEKOLAH DASAR - Putri, Nadya Prameski; Ridwanudin, Dindin (Elementar : Jurnal Pendidikan Dasar, 2024)
This research aims to find out the significance of the relationship self confidence and Indonesian learning outcomes in grade IV MI Al-Mursyidiyyah. This research was conducted in January until March 2023 at MI Al-Mursyidiyyah, Pamulang. The sampling technique is total sampling. The research instrument used was a questionnaire of self confidence and documentation of student’s Indonesian scores. Hypothesis testing in this research used the pearson product moment with correlation technique. The results found in this research that there is significance relationshop self confidence and Indonesian learning outcomes in grade IV MI Al-Mursyidiyyah, althought in the weak category. The results showed that the value of significance  0,006 < 0,05 and value of pearson correlation was 0,277 and was included in the weak category. While, the value of the coefficient of determination in this research show the figure of 7,67%. Therefore, there is a weak and significance relationship self confidence and Indonesian learning outcomes in grade IV MI Al-Musryidiyyah.